Concept of Regulating youth Migration Mobility of Ukraine in War Conditions - Mariana Bil; Oleksandr Makhoniuk; Nazariy Popadynets (Vasyl Stefanyk Precarpathian National University, 2022)
Problematic aspects of the synergy of youth and migration policy, which acquire additional relevance for Ukraine in the war conditions, in the article were considered. The aim of the article is the scientific substantiation of the conceptual provisions regarding the regulation of youth migration mobility with the detection of modern priorities for Ukraine. The analysis of the legislation of Ukraine in the social sphere made it possible to reveal the importance of the issue of state support for youth among the conceptual-strategic and program-target priorities. At a time when developed countries are actively promoting the idea of «Talent on the Move», youth migration in Ukraine is taking on threatening characteristics due to the lack of systematic regulation of it. The results of a sociological survey of young people with migration experience, based on the example of the Lviv region of Ukraine, proved that youth re-emigration intentions were extremely low even before the Russo-Ukrainian War 2022. The emigration of Ukrainian youth is intellectualizing, changing the previous migration labor wave. The current wave of forced emigration also has the face of children and youth, who are highly likely to successfully integrate into host societies. Taking into account the risks of irreversible demographic losses and the social functionality of the state, it is necessary to implement a new concept of regulating the youth migration mobility, which includes measures to influence migration movements and migration potential, as well as support for the main areas of youth life. The new concept should be developed in accordance with the regulated priorities of national security, human and sustainable development, the expediency of youth policy regionalization in the conditions of a successful decentralization reform. The basis of the migration potential regulation is the organization of migration mobility monitoring in the context of the development and capitalization of human potential, that is, the clarification of the consequences of migration for the person and the region (state) of origin. It is mandatory to support of social ties with diaspora institutions. The new concept of regulating the youth migration mobility should aim to stimulate their re-emigration with a promising transition to ensuring circular migration during the post-war recovery period of Ukraine. The obtained results are the basis for further research in the part of determining the mechanisms of stimulating the re-emigration of young people to Ukraine and attracting their potential during further stay abroad.